Evaluation of photosynthetic Taxa in the Venice Lagoon from the nineteenth century to present day - Drigo, Filippo; Stefanelli, Chiara; Moro, Isabella; De Pittà, Cristiano (Frontiers in Marine Science, 2024)
The Venice Lagoon is the largest transitional environment within the Mediterranean Sea (almost 550 km2). Being a transitional environment, it contains many different ecological niches, hence the biodiversity in this environment is very high. However, at the same time, this lagoon system is under constant pressure from human activities, and it has been greatly modified by humans during the centuries. Examples are the construction of the city of Venice, the digging of the canals for commercial ships, and the modifications of the three inlets to the lagoon. All these activities altered the circulation inside the lagoon, modifying the equilibrium between river and sea inputs, also influencing the sediment intake, fundamental for saltmarshes stability. During the centuries, many authors monitored the photosynthetic taxa (seaweeds, halophytes, and seagrasses) inhabiting the Venice Lagoon. In this study, we reviewed works from the nineteenth century to the present time to obtain a complete and updated view of the photosynthetic species that inhabit this environment, observing a decrease in the presence of charophytes and heterokontophytes and an increase in rhodophytes in the analyzed period. Moreover, we also considered the ecological valence of the species reported in this environment through two different ecological indexes (Macroalgae Quality Index – MaQI, Ecological Evaluation Index – EEI), observing a decrease in the relative contribution of the species with high ecological valence along the centuries. We also reviewed the presence of threatened and non-indigenous species, observing some differences in the considered works. Finally, we also considered the molecular resources available on online databases, finding only half macroalgal species with a reference sequence, compared to almost 90% for higher plants.